A Case Study of Students’ Difficulties in Learning Conditional Sentence at the Eleventh Grade Students’ of SMA N 4 Purworejo in the Academic Year of 2016/2017 - Satmoko Puji Laksana (Scripta : English Department Journal, 2019)
Conditional sentence becomes one of materials in grammar that is complex and difficultto be used by the students especially in senior high school. Identifying the difficulties ofconditional sentence is essential to know how well the students master the materials.The objectives of this research are to describe the most difficult types of conditionalsentence used by the students and to identify why the students get difficulties in learningconditional sentence. This research uses descriptive qualitative research. The subject ofthis research is the eleventh grade students (Class XI Bahasa) of SMA N 4 Purworejo.From the findings that the researcher has done, conditional sentence type 3 became themost difficult one. Based on the test, for each type of conditional sentence, type 3 is thehighest with the total number of wrong answer are 116 (47.5%), then type 2 with thetotal number of wrong answer are 84 (34.4%), while type 1 is the lowest with the totalnumber of wrong answer are 44 (18.1%). Added by the result of questionnaire assupporting instruments, the most difficult type of conditional sentence is conditionalsentence type 3. The result shows that three students strongly agree and twentystudents agree that conditional sentence type 3 is difficult. Then, one student stronglyagrees and fourteen students agree that conditional sentence type 2 is difficult. While,just nine students agree that conditional type 1 is difficult. Morever, from the result ofthe interview and questionnaire, the researcher identifies the students’ difficulties inlearning conditional sentence, they are the highest graduation is students are lack ofvocabulary (66.67%), the second is having to eagerness to master the material (62.34%),the third is having negative attitude toward teaching and learning process (56.79%), thefourth is environment impact to learn English (55.55%), the fifth is not paying attentionto the material (50.93%), the sixth is having negative attitude towards English andgrammar (54.32%), and the last is the condition of the facilities is not good (22.22%).